(3TQM eNJUQ GdSfhSj aj GdefWbs - (3GdSfhSj, eMeO Hf jhSa Hf YeQ, J (B895 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd CHh YHO Gddg eMeO Hf jhSa GdMSfj GdSfhSj GdMeO ddg Gdedc GdhgGH hHYO agPG JbjjO bUOJ Hg TQM eNJUQj aj Yde GdefWbs
(3BNQgG (B:s
(3hdG jfJL GSJKfGA Yjf TjA ePgeG dLhGR GLJeGYgeG Ydi GdUOa adeGfYI GdNdh EPG GdfJjLJGf GdCNjQJGf fJGjL GdMbjbIs
(3Chdg aGFOI aj GdJUhas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 154s
(3eYLe GdeDdajf (B3 / 786s
(3gOjI GdYGQajf (B2 / 216s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs